Agriculture Policy Scores of Selected Countries Through the Technique for Order of Preference (TOPSIS) Method - Madiyoh Abdulhakim (Sciendo, 2021)
The purpose of this paper is to demonstrate the performance of agricultural sectors in the Association of Southeast Asian Nations (ASEAN) countries using selected criteria, to identify the deficiencies in agricultural policies, to explore competitive advantages and to guide food and nutrition policies. The analyses of this research use the secondary of time series data between the years 1967 - 2016 from 10 countries including; Brunei Darussalam, Cambodia, Indonesia, Laos PDR, Malaysia, Myanmar, Philippines, Singapore, Thailand and Vietnam which are the member of ASEAN. This research uses the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method and the data used for the mentioned countries include the following criteria; total agricultural production value of the land, self-sufficiency of animal products criteria, self-sufficiency of crop products criteria, rural population rate, greenhouse gas emissions from agriculture, and value of foreign trade in agricultural products. The result of proximity coefficients calculated with the TOPSIS method, which according to the number of proximity and maximum benefit analysis should be done according to the order of preference. It is stated that Thailand, Philippines and Indonesia were the most successful countries in the agricultural policy performance in 1967. As for last decades, Malaysia became the most successful country in agricultural policy performance. We can infer from the results that Malay industrial sector triggered the agricultural sector by supplying financial investment atmosphere.